Safety nets and implementation of macroeconomic adjustment programmes - Gupta, Sanjeev; Inchauste, Gabriela; Clements, Benedict (2003)
Social safety nets are critical for mitigating the costs of crises and adjustment programmes. This paper reviews best practices in the design and implementation of safety nets. The main lessons suggest that the following are critical: having safety net instruments in place before crises occur; information on vulnerable groups to facilitate targeting; levels of spending that are adequate for this task yet consistent with sound macroeconomic policy; and administrative capacity. In this context, food-based safety nets can be an attractive option when administrative capacity is scarce, as they are conducive to self-targeting. In assessing options for minimising the adverse effects of policies on the poor and the need for social safety nets, poverty and social impact analysis (PSIA) can be a useful policy tool. In general, there is scope for more systematic PSIA and more effective social safety nets to minimise the costs of crises and adjustment programmes. The evidence so far also suggests that there is room for improving the role of global food aid as an international safety net. Global food aid is well-targeted, but the size and timing of disbursements have not been appropriate for meeting shortfalls in domestic food supply in recipient countries. - Reproduced.
Keywords: Macroeconomics